Kajian Kriminologis Ekploitasi Kemisikan dalam Pengemisan di Media Sosial - Isnawan, Fuadi (Wajah Hukum, 2023)
Technological developments in society as a real impact on life cannot be denied anymore. Apart from being able to bring good benefits or impacts, the phenomenon of this technological development can create various things that have never existed before. Especially when associated with earning income on social media as existing technological developments. The phenomenon that has emerged recently is the phenomenon of online begging in social media which is rife. This phenomenon makes some content creators tempted to earn money in a much easier way by relying on the compassion of their audience. In this paper, we will examine the reasons behind this action and what efforts can be made to overcome this. The method used is a normative juridical method which will examine the criminological factors behind this begging phenomenon on social media. It will also examine the various efforts made to overcome it. From this paper it is found that the poverty factor is the main driving factor. Besides that, the popularity factor in a short time and low awareness and legal compliance in the community are driving forces for this to happen. Efforts are made by instilling morals in society, legal counseling and the use of criminal law strictly.